REDESAIN JALUR PEDESTRIAN JALAN DIPONEGORO SALATIGA BERDASARKAN ASPEK VISUAL, FISIK, DAN KENYAMANAN TERMAL (Jurnal Arsitektur ARCADE, 2026)
The landscape transformation of the Jalan Diponegoro corridor in Salatiga from 1925 to 2025 has altered its physical form, visual quality, and thermal comfort due to changes in vegetation and the conversion of public open spaces. This study aims to examine the impact of pedestrian path changes in terms of physical condition, aesthetics, and thermal comfort. The research is exploratory, with the variables being visual quality, thermal comfort, and aesthetics. Descriptive statistics were used for data analysis. The study was conducted at eight observation points. A comparison of visual assessments between 1925 and 2025 indicated a decline in visual quality in 2025 at several segments, such as near Satlantas and beside KFC, caused by sidewalk damage from mahogany tree roots and visual irregularities. In addition, thermal comfort was categorized as uncomfortable, especially during midday, while the physical condition of pedestrian paths showed poor inclusive accessibility for people with disabilities. Based on these findings, the alternative solution proposed is a redesign of the pedestrian paths with a “Green Heritage Corridor” concept. The objectives are to strengthen the area’s identity, create a pedestrian corridor that is human-centered, inclusive, and disability-friendly, and to improve the quality of green open spaces.
Keywords: Urban Landscape, Public Space, vegetation